2018
DOI: 10.1055/a-0592-6550
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-ESI-MS Characterization of Certain Polyphenolic Compounds of Carica papaya L. Fruit Extracts and Evaluation of Their Potential Against Murine Schistosomiasis mansoni

Abstract: The antischistosomal activities of L. extracts were evaluated and the characterization of the active secondary metabolites of the defatted methanolic extract was performed using HPLC-ESI-MS. The plant fruit powders were extracted with 85% methanol and fractionated using organic solvents. The antischistosomal effects of the methanolic extracts and its fractions, as well as the assessment of the relationship between the antischistosomal activity of these plant extracts and oxidative stress, was determined. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Aqueous extracts of C. papaya seeds caused a significant reduction in parasite burden of the mice attributed to the papain, which is capable of digesting bacteria and parasitic cells, hence its use as anthelmintic and antibiotic (Fajimi and Taiwo 2005). Abdel-Lateef et al (2018) reported that oral administration of defatted MeOH extract of C. papaya fruits (500mg/kg) decreased Schistosoma mansoni number in CD-1 mice by 36.4% and ova in intestine and liver tissues by 39.7% & 49.8%, respectively, but lower than praziquantel (94-96%). Also, the protective capacity of oral administration of crude extracts, MeOH, EtOAc or BuOH of C. papaya (100mg/kg) to mice infected with S. mansoni was 60.3%, 38.7%, 68.2%, & 52.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aqueous extracts of C. papaya seeds caused a significant reduction in parasite burden of the mice attributed to the papain, which is capable of digesting bacteria and parasitic cells, hence its use as anthelmintic and antibiotic (Fajimi and Taiwo 2005). Abdel-Lateef et al (2018) reported that oral administration of defatted MeOH extract of C. papaya fruits (500mg/kg) decreased Schistosoma mansoni number in CD-1 mice by 36.4% and ova in intestine and liver tissues by 39.7% & 49.8%, respectively, but lower than praziquantel (94-96%). Also, the protective capacity of oral administration of crude extracts, MeOH, EtOAc or BuOH of C. papaya (100mg/kg) to mice infected with S. mansoni was 60.3%, 38.7%, 68.2%, & 52.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Amazu et al (2010) reported anti-inflammatory activity of the methanolic extract of the seeds of C. papaya in experimental animals, they interpreted these data by inhibitory action of extract against some mediators such as histamine, prostaglandins, nitric oxide, cytokines, platelets activating factor. HPLC-ESI-MS analysis of methanolic extract of C. papaya fruit caused a first-ordered compound p-hydroxybenzoic acid-tri-O-hexoside which is isomeric with 2-hydroxybenzoic or salicylic acid, a precursor to aspirin (Abdel-Lateef et al, 2018). The latter is a medication used to reduce pain, fever, or inflammation, so, anti-inflammatory effect of MeOH papaya fruit extract was attributed for the presence of p-hydroxybenzoic-acid-tri-O-hexoside in large amount in the extract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, methanol extracts from different plants have been reported for their antischistosomal effects, such as those obtained from Eucalyptus globulus, 20 Furcraea selloa, 21 Jatropha curcas, 22 Momordica balsamina, 23 Carica papaya. 24 Actinopyga echinites, and Holothuria polii. 25 Many compounds isolated from methanol extracts have also been reported for their antischistosomal activities, such as the steroidal glycoside (saponin), 21 S. mansoni miracidia.…”
Section: Discussionmentioning
confidence: 99%
“…Host-parasite interactions in schistosomiasis help in understanding many important facts of the liver fibrosis (Andrade, 2009). The inflammatory granuloma formation around deposited eggs; granulomas were composed of macrophages, eosinophils and lymphocytes with proportion of cells varied in different organs characterizing schistosomiasis (Abdel-Lateef et al, 2018). Granuloma formation is a cellmediated immune response dependent on CD4+ T cells sensitized to schistosomal egg antigens.…”
Section: Introductionmentioning
confidence: 99%